Fiscal Reform in European Economies in Transition - Kopits, George (IMF Working Papers; Working Paper ;, 1991)
Most European economies in transition are engaged in public sector reform aimed mainly at replacing the previous fiscal system subordinated to the central plan with a system where fiscal instruments can make a distinct contribution to stabilization, equity, and efficiency. This paper examines past progress and future tasks in major reform areas: taxation, subsidies, social security, public investment, public enterprises, government debt, and intergovernmental relations. An overview of the fiscal reform process suggests that the contraction and restructuring of government operations are not likely to materialize soon and that there is a serious risk of widening fiscal imbalances during the transition.